AI as a Teaching Assistant: An Innovative Approach to Education Through Customized Model Answer Generation and Guided Practice - Olędzka , Monika; Benesio Carace , Mark; de Oliveira Tomaz , Susana; Pan , Benny; Jiang , Pengfei (Studia Edukacyjne, 2024)
Artificial Intelligence (AI) is rapidly becoming an integral tool in modern education, offering opportunities to personalize learning, optimize teaching strategies, and enhance critical thinking skills. This paper explores the role of AI as a teaching assistant, focusing on the project “Generating Customized Model Answers as Revision Guides Using AI” conducted within the 17th ASEF Classroom Network School Collaboration. The study analyzes the impact of AI-generated model answers on student preparation for exams, highlighting improvements in student performance, particularly in tasks requiring analysis and synthesis of information. Through personalized feedback, adaptive content delivery, and interactive simulations, AI fosters deeper analytical engagement and prepares students for real-world challenges. Despite its transformative potential, the study emphasizes the importance of complementing AI with traditional teaching methods to fully develop students’ skills. Additionally, the ethical considerations of aligning AI systems with human values remain critical to ensuring their positive societal impact. This research underscores AI’s pivotal role in the future of education while advocating for its responsible implementation.